Report on NEMO Training Course ‘Regional Development through Heritage in Sweden’ in Östersund, Sweden - Anenmarie Pothaar (EXARC, 2018)
EXARC is an associated member of NEMO, the Network of European Museum Organisations. ‘The leading principle of NEMO’s activities for members is to empower the network to help professionalise museum and heritage work though exchanging and discussing with colleagues from other countries.’ (www.ne-mo.org). Annemarie Pothaar is an EXARC Board member with a special interest in Interpretation, who was invited to send in a letter of motivation and expectation, to attend the NEMO training course. She was selected to attend the one day training course on 29th June 2018 in Östersund Sweden. This was facilitated by the Jamtli Foundation and the Nordic Centre of Heritage Learning and Creativity (NCK). The meeting was attended by six colleagues coming from different countries, including the Netherlands and Azerbaijan. The theme of the meeting was how heritage can contribute to regional development, including the educational impact, but also working towards cultural diversification and economic development.